Knowledge and perceptions of antimicrobial resistance and antimicrobial stewardship among staff at a national cancer referral center in Uganda - Elizabeth A. Gulleen; Margaret Lubwama; Alfred Komakech; Elizabeth M. Krantz; Catherine Liu; Warren Phipps (Cambridge University Press, 2022)
Abstract Objectives: As access to cancer care has improved throughout sub-Saharan Africa, treatment-associated infections have increased. Assessing healthcare worker knowledge of antimicrobial stewardship and identifying the barriers to infection management will inform the development of contextually appropriate antimicrobial stewardship programs, improving cancer outcomes in sub-Saharan Africa. Design: Cross-sectional survey. Setting: The Uganda Cancer Institute (UCI), a national cancer referral center in Kampala, Uganda. Participants: We surveyed 61 UCI staff: 29 nurses, 7 pharmacists, and 25 physicians. Methods: The survey contained 25 questions and 1 ranking exercise. We examined differences in responses by staff role. Results: All 60 respondents who answered the question had heard the term "antimicrobial resistance." Only 44 (73%) had heard the term "antimicrobial stewardship." Nurses were less likely than pharmacists or physicians to be familiar with either term. Also, 41 respondents (68%) felt that loss of antibiotic susceptibility is a major issue at UCI. Regarding barriers to diagnosing infections, 54 (93%) of 58 thought that it was difficult to obtain blood cultures and 48 (86%) of 56 thought that it was difficult to regularly measure temperatures. Conclusions: Although most recognized the term "antimicrobial resistance," fewer were familiar with the term "antimicrobial stewardship." Inappropriate antibiotic use was recognized as a contributor to antimicrobial resistance, but hand hygiene was underrecognized as a contributing factor. We identified numerous barriers to diagnosing infections, including the ability to obtain blood cultures and consistently monitor temperatures. Educating staff regarding antimicrobial selection, allocating resources for blood cultures, and implementing strategies to enhance fever detection will improve infection management.